Association among Fraction of Exhaled Nitrous Oxide, Bronchodilator Response and Inhaled Corticosteroid Type - Ryan W Smith; Kim Downey; Nadia Snow; Sharon Dell; W Gary Smith (Canadian Respiratory Journal)
BACKGROUND: Fraction of exhaled nitrous oxide (FeNO) is a known marker of airway inflammation and a topic of recent investigation for asthma control in children.